1997
DOI: 10.1046/j.1365-2222.1997.1800979.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of interferon‐gamma (IFNγ) as a candidate gene for asthma

Abstract: The gene for IFNgamma appears to be highly conserved as no sequence variations were detected in 265 individuals. These results suggest that mutations of the IFNgamma gene are unlikely to be a significant cause of an inherited asthma diathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Studies using a HCV replicon system showed that IFN-γ is capable of inhibiting the HCV replication [58]. Similar to other cytokines there is no polymorphism reported in the coding region; but the non-coding region possesses frequent polymorphisms which are implicated in several chronic inflammatory conditions and autoimmune diseases [59,60]. It is reported that the SNP –764G of IFN-γ which is located in the proximal promoter region was strongly associated with SVR in case of HCV infection because the G allele conferred a two to three-fold increase in the promoter activity.…”
Section: Snps Of Host Genesmentioning
confidence: 99%
“…Studies using a HCV replicon system showed that IFN-γ is capable of inhibiting the HCV replication [58]. Similar to other cytokines there is no polymorphism reported in the coding region; but the non-coding region possesses frequent polymorphisms which are implicated in several chronic inflammatory conditions and autoimmune diseases [59,60]. It is reported that the SNP –764G of IFN-γ which is located in the proximal promoter region was strongly associated with SVR in case of HCV infection because the G allele conferred a two to three-fold increase in the promoter activity.…”
Section: Snps Of Host Genesmentioning
confidence: 99%
“…435 No polymorphisms of the IFN-γ gene have been associated with asthma 436. Administration of exogenous IFN-γ prevents the airway eosinophilia and hyperresponsiveness following allergen exposure in mice 437…”
Section: Inhibitory Cytokinesmentioning
confidence: 99%
“…An association between a SNP in NOS1 and eosinophil count was also shown in German/ Swedish patients (Immervoll et al 2001). Hyden et al (1997) reported that no polymorphism in the IFNG was associated with atopic asthma, whereas an association between the GT repeat in intron 1 of IFNG and childhood asthma was suggested in the Japanese population (Nakao et al 2001). Heinzmann et al (2000a) screened polymorphisms in SCF, STAT6, TR2 (thyroid receptor 2), and LTA4H and found two polymorphisms in SCF and one in TR2 in the German population.…”
Section: Introductionmentioning
confidence: 99%